The Influence of Foreign Currency Volatility on Stok Return and Cash Flows: An Empirical Study in Indonesia Listed Companies - Nyoman Ardhianta Putera; Zuni Barokah (The Indonesian Journal of Accounting Research, 2018)
Abstract:This study investigates the impact of foreign currency volatility on companies' stocks returns and cash flow. Based on the analysis of 184 companies during January 2011 – December 2015, we find significant associations between foreign currency volatilities (REER) and companies’ stock returns. Further, we also find significant associations between foreign currency volatilities (REER, USD, JPY, EUR) and companies' quarterly cash flows. However, further inspection by using annual financial statements to replace quarterly cash flows reveals that only REER has a significant association with annual cash flows. Although the difference findings could be due to a smaller number of samples included in the model using annual cash-flows (n=920) which is much smaller than the model incorporating quarterly cash-flows (n=3,660), the findings may also indicate that the effect of foreign currency volatility is more pronounced to the more timely financial statements and is dissipated overtime in the annual financial statements. Overall, the findings are consistent with previous studies of Booth & Rotenberg (1990), Bartram (2008), and Atanasov & Nitschka (2015) which suggest that corporate cash flows are subject to foreign currency volatilities and companies’ future cash flow might be disturbed due to unexpected exchange rates changes.Abstrak: Studi ini menyelidiki dampak dari volatilitas mata uang asing pada pengembalian saham perusahaan dan arus kas. Berdasarkan analisis 184 perusahaan selama Januari 2011 - Desember 2015, kami menemukan hubungan yang signifikan antara volatilitas mata uang asing (REER) dan pengembalian saham perusahaan. Selanjutnya, kami juga menemukan hubungan yang signifikan antara volatilitas mata uang asing (REER, USD, JPY, EUR) dan arus kas kuartalan perusahaan. Namun, pemeriksaan lebih lanjut dengan menggunakan laporan keuangan tahunan untuk menggantikan arus kas kuartalan mengungkapkan bahwa hanya REER yang memiliki hubungan signifikan dengan arus kas tahunan. Meskipun temuan perbedaan bisa disebabkan oleh sejumlah kecil sampel yang termasuk dalam model menggunakan arus kas tahunan (n = 920) yang jauh lebih kecil daripada model yang menggabungkan arus kas kuartalan (n = 3.660), temuan juga dapat menunjukkan bahwa efek dari volatilitas mata uang asing lebih nyata pada laporan keuangan yang lebih tepat waktu. Secara keseluruhan, temuan konsisten dengan studi sebelumnya Booth & Rotenberg (1990), Bartram (2008), dan Atanasov & Nitschka (2015) yang menunjukkan bahwa arus kas perusahaan tunduk pada volatilitas mata uang asing dan arus kas masa depan perusahaan mungkin terganggu karena perubahan nilai tukar yang tidak terduga.